MEMBANGUN BUDAYA LITERASI MEMBACA UNTUK MENINGKATKAN KUALITAS HIDUP GENERASI ALFA DI KELURAHAN KILASAH - Khaeruman, Khaeruman; Kusuma, Jaka Wijaya; Dewi, Irma Nurmala; Tabroni, Tabroni; Hanafiah, Hafidz (Yayasan Education and Social Center, 2025)
The Community Service Program (PKM) with the theme “Building a Reading Literacy Culture to Improve the Quality of Life Habits of Generation Alpha in Kilasah Village” aims to improve reading habits among Generation Alpha children in Kilasah Village, as well as strengthen the role of parents and teachers in supporting literacy. Literacy training involving children, parents, and teachers was conducted through a participatory approach that included the provision of reading books, training in creative learning methods, and the formation of reading habits at home. The results of the training showed a significant increase in children's reading habits, as well as the involvement of parents and teachers in supporting children's literacy. In addition, the mobile library has succeeded in providing wider access to reading books, although challenges related to internet access and time remain obstacles that need to be overcome. This program has succeeded in having a positive impact in creating a sustainable literacy culture in Kilasah Village, with the potential to improve the quality of life of children through healthy reading habits.